C = 4M + 5
4M = C - 5
M = (C - 5)/4
answer is D. Last one.
C. Is try correct answer
See example in the attached picture
Answer:
1. 8x+9
2. 3x + 11
3. 9x + 8
4. 11x+9
5. 6x
6. 10x+ 8
7. 7x+7
Step-by-step explanation:
Answer:
![\displaystyle y-5=-\frac{10}{9}(x+6)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-5%3D-%5Cfrac%7B10%7D%7B9%7D%28x%2B6%29)
Or:
![\displaystyle y+5=-\frac{10}{9}(x-3)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%2B5%3D-%5Cfrac%7B10%7D%7B9%7D%28x-3%29)
Step-by-step explanation:
We want to write the equation of a line that passes through the points (-6, 5) and (3, -5) in point-slope form.
Point-slope form is given by:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
Thus, first, we need to find the slope. We can use the slope formula:
![\displaystyle m=\frac{\Delta y}{\Delta x}=\frac{(-5)-(5)}{(3)-(-6)}=\frac{-10}{9}=-\frac{10}{9}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20m%3D%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D%5Cfrac%7B%28-5%29-%285%29%7D%7B%283%29-%28-6%29%7D%3D%5Cfrac%7B-10%7D%7B9%7D%3D-%5Cfrac%7B10%7D%7B9%7D)
Next, we can use either of the two given points. I'll use (-6, 5). So, let (-6, 5) be (<em>x₁, y₁</em>). Substitute:
![\displaystyle y-(5)=-\frac{10}{9}(x-(-6))](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-%285%29%3D-%5Cfrac%7B10%7D%7B9%7D%28x-%28-6%29%29)
Or, fully simplified:
![\displaystyle y-5=\frac{-10}{9}(x+6)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-5%3D%5Cfrac%7B-10%7D%7B9%7D%28x%2B6%29)
Using the other point, we will acquire:
![\displaystyle y-(-5)=-\frac{10}{9}(x-(3))](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-%28-5%29%3D-%5Cfrac%7B10%7D%7B9%7D%28x-%283%29%29)
Or, simplified:
![\displaystyle y+5=-\frac{10}{9}(x-3)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%2B5%3D-%5Cfrac%7B10%7D%7B9%7D%28x-3%29)
Answer:
3rd option, (3,6) (5,10) (8,1) (14,1)
Step-by-step explanation: